Development of an Information System for Practicum Video Content in the Digital Library of KH. A. Wahab Hasbullah University - Faht, Nur; Khafidhoh, Nur (KH. A. Wahab Hasbullah University, 2025)
A library is a work unit of a particular agency or institution that manages library materials, either in the form of books or non-book materials, that are systematically arranged according to specific rules so that they can be used as a source of information by each user. Although books remain a valuable source of information, many faculties, especially in fields that require practicums, often face difficulties when courses are completed, especially for students who are late to class or absent due to reasons such as work or other commitments. This challenge is even more pronounced for students who are unfamiliar with the course, especially those without a basic education in the field. Additionally, this website is also expected to support students in learning independently after lectures have concluded. The method used in planning research on the video content development system for practical work at the Unwaha digital library is the Waterfall Model, which encompasses analysis, design, testing, implementation, and maintenance phases. In data collection, quantitative methods are employed, including questionnaires and embedded techniques to collect video data. The results of this study indicate that 50% of the respondents considered this video tutorial website to have a significant influence on their learning motivation. Additionally, 54.2% of respondents considered this video tutorial website effective in supporting distance learning.